Resource-usefulness approach to the study of socio-economic systems as a theoretical basis for their safe development - Bainev, Valerii F.; Gorayeva, Tatyana Yu. (Journal of the Belarusian State University. Economics, 2023)
In connection with the unprecedented aggravation of the geopolitical situation and the aggravation of global contradictions in the development of civilisation, the tasks of ensuring and strengthening security are coming to the fore. The fundamental shortcomings of the prevailing cost, inherently costly economic paradigm, which prevent humanity from entering the trajectory of safe sustainable development, are revealed. As an addition to the cost criteria for assessing and managing socio-economic systems, useful ones that focus not on costs, but on the useful result of the functioning of socio-economic systems are proposed. It is shown that the use of a resource-usefulness approach to the assessment and management of the scientific and technical sphere can solve the urgent problem for Belarus of strengthening technological security. It is concluded that the resource-utility approach can become the theoretical basis for civilisation to enter the trajectory of safe, sustainable development.